Regulation in collaborative writing to solve a PBL in Biology - González Lillo, Emmy Antonella (2024)
Collaborative writing is a complex task that involves diverse regulatory processes. In this case study we address the resolution of Problem-Based Learning through a report written collaboratively. Ten students from the Human Biology degree and their tutor took part. We collected data inside the classroom (the writing assignment, the assessment rubric, and audio recordings of 3 tutorials) and data outside the classroom (screen recordings of the students’ activity on their computers, the team’s WhatsApp group conversation, the final text of the written work, a focus group recording and the evaluative comments of the marking teachers). The results indicate that the processes of self-regulation and socially shared regulation are the most developed. Participants demonstrate control and autonomy in carrying out individual and group activities. On the other hand, co-regulation is less frequent, as the teacher’s mediation, the writing assignment, and the evaluation instruments could be more specific in relation to the task to be carried out. Consequently, it is necessary to generate gender-specific mediation and evaluation tools to improve collaboration among students when writing.